5G URBAN CELL PLANNING ESTIMATION AND BASE STATION THROUGHPUT DETERMINATION - AHMED , KAWAN FAIQ; AL-HINDAWI, ASAAD MUBDIR JASSIM (Journal of Duhok University, 2023)
Operators need to consider several factors that could impact a network's profitability with the increasing demand for 5G wireless telecommunications. These factors include the environment, base station layouts, and frequency scheme patterns. 5G systems promise low-power devices, comparable coverage strategies, high dependability, low latency, and a million-fold increase in scheme capacity over current networks. The first and most crucial step in creating a 5G network and radio network design is to calculate the number of cells in a specific area. To estimate the number of cells, this article utilizes the Radio Link Budget (RLB) computation method to calculate each cell's maximum permitted path losses. Additionally, determining the number of 5G base stations required to cover an area and maximize cell performance adequately necessitates carefully evaluating the center frequency, 3GPP propagation model, maximum permitted route losses, and channel bandwidth. To accomplish this, four different scenarios have been considered, using four different center frequencies, and for each scenario, two 3GPP propagation models (Urban Macro 3D-UMa NLOS and Urban Micro 3D-UMi NLOS) are utilized to find the estimated 5G cell number for an urban area of 4 km2. This article emphasizes the importance of carefully considering several variables, such as the center frequency, 3GPP propagation model, maximum permitted route losses, and channel bandwidth, to ensure reliable signal transmission and reception, high data rates, and efficient utilization of network resources—further the more. The second objective of this article is the 5G new radio throughput calculation, which is essential for determining the sufficient fronthaul link data rate required for planned C-RAN and 5G cell structures.